A Within-Subject Pilot Feasibility Study of a Gambling Specific SBIRT Intervention Delivered in an Urban HIV/Primary Clinic - Heinlein, Emily; Rugle, Lori; Potts, Wendy; Welsh, Chris; Himelhoch, Seth (Journal of gambling studies, 2022)
Background Although there are few interventions available to provide screening and brief intervention targeted toward problematic gambling, Screening, Brief Intervention and Referral to Treatment (SBIRT) is an evidence-based intervention that has demonstrated effectiveness in reducing gambling behaviors. Methods The goal of this pilot study was to evaluate the feasibility, acceptability and preliminary outcomes of a gambling specific SBIRT intervention in a medical setting. Fifteen participants were recruited from an urban HIV/Primary Care clinic to receive the gambling specific SBIRT intervention delivered by 3 clinicians. Process and gambling specific outcome measures were evaluated at baseline, immediately after the intervention and at 1-month follow-up. Results On average, patient participants were 49 years and self-described themselves as male (60%) and Black or African American (86.7%). Three (20%) participants met 4 or more criteria of the DSM-5 gambling disorder. Compared to baseline, those who participated in the intervention decreased both the median number of days gambled (1 days vs. 0 days), as well as the median money gambled at 1-month follow-up ($7 vs. $1). Participants with 4 or more criteria of DSM-5 gambling had the greatest reduction (days gambled: (26 days vs. 21 days); money spent: (($400 vs. $65)). Participants reported that the intervention was acceptable. Clinician participants found the intervention to be easy to deliver. Conclusions A gambling specific SBIRT intervention was feasible to deliver and acceptable to participants. Gambling specific outcome measures were reduced at 1-month follow-up. A randomized control trial to evaluate the efficacy of the intervention is a recommended next step.